Does origin always matter? Evaluating the influence of nonlocal seed provenances for ecological restoration purposes in a widespread and outcrossing plant species. Issue 23 (17th November 2015) - Reiker, Jutta; Schulz, Benjamin; Wissemann, Volker; Gemeinholzer, Birgit
Abstract: For restoration purposes, nature conservation generally enforces the use of local seed material based on the "local‐is‐best" (LIB) approach. However, in some cases recommendations to refrain from this approach have been made. Here we test if a common widespread species with no obvious signs of local adaptation may be a candidate species for abandoning LIB during restoration. Using 10 microsatellite markers we compared population genetic patterns of the generalist species Daucus carota in indigenous and formerly restored sites (nonlocal seed provenances). Gene diversity overall ranged between H e  = 0.67 and 0.86 and showed no significant differences between the two groups. Hierarchical AMOVA and principal component analysis revealed very high genetic population admixture and negligible differentiation between indigenous and restored sites ( F CT  = 0.002). Moreover, differentiation between groups was caused by only one outlier population, where inbreeding effects are presumed. We therefore conclude that the introduction of nonlocal seed provenances in the course of landscape restoration did not jeopardize regional species persistence by contributing to inbreeding or outbreeding depressions, or any measurable adverse population genetic effect. On the basis of these results, we see no obvious objections to the current practice to use the 10‐fold cheaper, nonlocal seed material of D. carota for restoration projects. Abstract : We asked whether the "local‐is‐best" approach does also apply for conservation projects of common and widely distributed species. Comparing indigenous and restored populations of the generalist plant species Daucus carota we found no distinct differences in genetic diversity and differentiation between the two groups.